2014
DOI: 10.1038/bjc.2014.430
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant predicts bevacizumab-induced hypertension in ECOG-5103 and ECOG-2100

Abstract: Background:Bevacizumab has broad anti-tumour activity, but substantial risk of hypertension. No reliable markers are available for predicting bevacizumab-induced hypertension.Methods:A genome-wide association study (GWAS) was performed in the phase III bevacizumab-based adjuvant breast cancer trial, ECOG-5103, to evaluate for an association between genotypes and hypertension. GWAS was conducted in those who had experienced systolic blood pressure (SBP) >160 mm Hg during therapy using binary analysis and a cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
(34 reference statements)
0
27
1
1
Order By: Relevance
“…15,17,18 In this study we have compared the likelihood of each of these clinically relevant toxicities between AAs and EAs. We report a numerically higher likelihood for each of these toxicities for AA's; with odds ratios ranging from 1.4-2.9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,17,18 In this study we have compared the likelihood of each of these clinically relevant toxicities between AAs and EAs. We report a numerically higher likelihood for each of these toxicities for AA's; with odds ratios ranging from 1.4-2.9.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide SNP arrays (either Illumina HumanOmni1-Quad or Human OmniExpress) were performed in two distinct study subsets as described previously. 15 A principal component analysis was performed using Eigenstrat and reference data from 11 HapMap phase III populations to identify clusters using the first two eigenvectors computed using all SNPs. 16 Samples clustering with those of African Ancestry (AA) and those of European Ancestry (EA) were used in these analyses; Supplemental figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have shown increased susceptibility of African Americans to bevacizumab-related hypertension; one showing a 1.6-fold increase in bevacizumab-induced hypertension (14), and a second showing bevacizumab-induced exacerbation of pre-existing hypertension disproportionately affecting African Americans (28). The former study included a GWAS of bevacizumab-induced hypertension which excluded the African American sample during quality control to avoid confounding population substructure (29). …”
Section: Ancestral Differences In Prevalence Of Chemotherapeutic Toximentioning
confidence: 99%
“…Ten single nucleotide polymorphisms (SNPs) were associated with bevacizumab-induced hypertension (p £ 0.05) but none of these overcome the threshold of multiple logistic regression (p < 0.0002). Conversely a genomewide association study in two randomized Phase III breast cancer trials (ECOG-5130 and ECOG-2100) revealed a compelling association between bevacizumab-induced grade 3/4 hypertension and an SNP in SV2C (rs6453204) (p = 0.037; Odds Ratio = 2.4) [51].…”
Section: Toxicitymentioning
confidence: 99%